Validation of the Leeds Assessment of Neuropathic Symptoms and Signs Pain Scale (LANSS) in Russia - D. G. Yusupova; N. A. Suponeva; A. A. Zimin; A. B. Zaytsev; M. Bennett; N. V. Belova; A. O. Gushcha; A. O. Chechotkin; G. A. Gatina; N. V. Polekhina; Pratish Bundhun; V. M. Ashrafov; et al. (Нервно-мышечные болезни, 2018)
Background. Objectivization of the characteristics of neuropathic pain is an important component of differential diagnosis in various diseases. Scales and questionnaires are topical diagnostic tools for assessing subjective symptoms for patients and health professionals.Objective to development and validation of the Russian version of the the Leeds Assessment of Neuropathic Symptoms and Signs Pain Scale (LANSS).Materials and methods. The study included two stages: linguocultural ratification and assessment of the psychometric properties of the developed Russian version.Results. The study showed a high level of reliability, validity and sensitivity of the developed Russian-language version of the scale. Conclusion. By the results of the study, the official validated Russian-language version of the scale is presented and recommended for use in work with Russian-speaking patients.